The moderation role of the audit committee in the relationship of audit reputation and audit tenure with audit quality - Thoha, Muhammad Nuur Farid; Handayani, Mutiara Ekka Suci (Journal of Economics and Business Letters, 2023)
This study aims to determine the effect of accounting firm reputation and audit tenure on audit quality and analyze audit committees to strengthen or weaken the relationship between accounting firm reputation and audit tenure. The population in this study are property and real estate sector companies listed on the Indonesia Stock Exchange in their 2016-2021 financial statements. The sampling technique in this study used a purposive sampling method and obtained a sample of 45 companies. The analysis technique used is regression logistic analysis and Moderated Regression Analysis (MRA) using SPSS version 25.0. The result of this study indicates that accounting firm reputation does not affect audit quality, audit tenure has a positive effect on audit quality, and audit committee weakens the relationship between accounting firm reputation and audit tenure on audit quality.